Hydrodynamic moments due to water on ship deck - Błocki, Witold (Computer Assisted Methods in Engineering and Science, 2023)
An analysis of the ship stability requires computer simulations of the ship motions leading to its capsizing. The large amplitudes of roll motion of the ship are connected with phenomena of immersing of ship deck into water. These phenomena require to take into account additional moments connected with water on a deck. The paper presents a new method (1994) of calculating these additional moments. An approximate and simple calculation of the additional moments is based on the second principle of dynamics applied to an element of a water running off the deck. The additional moments applied in numerical simulations of the ship motions, change significantly the roll motion. The paper presents results obtained from computer simulations. Some of the results are compared with the results of an experiment done with the ship model.